Percepción de autosuficiencia hacia la inclusión en el futuro profesorado de Educación Física: un estudio en contexto chileno (Perception of self-sufficiency towards inclusion in future Physical Education teaching: a study in the Chilean context) - Martínez-Angulo, Carolina; Deneb, Estefanía; Pindal, Catalina; Gallardo-Fuentes, Francisco; Carter-Thuillier, Bastian; Peña-Troncoso, Sebastián (Retos, 2023)
La inclusión del alumnado con discapacidad en el proceso de Enseñanza-Aprendizaje (E-A) necesita considerar a todas y todos en los procesos formativos de las distintas disciplinas. En este cometido, el profesorado debe poseer las competencias necesarias para cumplir con esta misión; las que adquiere y experimenta en su Formación Inicial Docente. El objetivo del estudio es conocer la percepción de autoeficacia del alumnado universitario de Educación Física que cursa el último año de carrera para liderar acciones pedagógicas de carácter inclusivo en las clases de dicha asignatura. Bajo un enfoque cuantitativo, se utilizó un cuestionario “Percepción de autoeficacia hacia la inclusión en futuros maestros de Educación Física” para valorar la percepción de autosuficiencia hacia la inclusión en futuros maestros y maestras de Educación Física. Los resultados reflejan que el nivel de confianza del futuro profesorado se encuentra entre moderada y alta, no existiendo diferencias significativas entre las dimensiones del cuestionario (intelectual, motriz, auditiva y visual). Esto implica que mayoritariamente las y los estudiantes de Educación Física se consideran competentes en este ámbito, no obstante esto se contrapone con estudios anteriores donde se señala el déficit formativo que existe en torno a educción inclusiva en las universidades que preparan docentes de Educación Física en Chile. Palabras Clave: Inclusión, Discapacidad, Adaptación, Autoeficiencia, Educación Física. Abstract. The inclusion of students with disabilities in the teaching-learning process (T-L) needs to consider everyone in the formative processes of different disciplines. In this task, teachers must possess the necessary competencies to fulfill this mission, which they acquire and experience in their Initial Teacher Training. The objective of the study is to understand the self-efficacy perception of university students in Physical Education who are in their last year of the degree program to lead pedagogical actions of an inclusive nature in the classes of that subject. Under a quantitative approach, a questionnaire "Perception of self-efficacy towards inclusion in future Physical Education teachers" was used to assess the perception of self-sufficiency towards inclusion in future male and female Physical Education teachers. The results reflect that the level of confidence of future teachers is between moderate and high, with no significant differences between the dimensions of the questionnaire (intellectual, motor, auditory, and visual). This implies that the majority of Physical Education students consider themselves competent in this area, although this contrasts with previous studies that indicate the training deficit that exists around inclusive education in universities that prepare Physical Education teachers in Chile. Keywords: Inclusion, Disability, Adaptation, Self-Efficacy, Physical Education.